Pengembangan Media Pembelajaran Dasar Listrik dan Elektronika Berbasis Augmented Reality di SMK - Reza Prayuda; Fivia Eliza (Jurnal Pendidikan Teknik Elektro, 2020)
The learning process in class X TITL SMK Negeri 1 Kerinci is still centered on the teacher, the lack of active students during the learning process, students play gadgets during the learning process and do not pay attention to the material that the teacher delivers. The learning process is still teacher-centered, in terms of delivering material, the teacher is still very dependent on blackboard media so that students find it difficult to understand the material delivered by the teacher which affects student learning outcomes. Therefore, researchers developed Augmented Reality learning media to help increase students' interest in learning. The research aims to develop valid and practical Augmented Reality learning media. The research method used is R&D (Research and Development) with the 4D model (Define, Design, Develop, and Dissaminate). The instrument used was a validity questionnaire and a practicality questionnaire with class X TITL students and subject teachers as respondents. The average result of the validity value in filling out the validity questionnaire by the validator is categorized as valid. And in filling out the practicality questionnaire, the practicality value is obtained in the very practical category. Based on the results of the development research carried out, it produces Augmented Reality learning media that is valid and very practical in Basic Electrical and Electronics subjects.